Optimizing the Multiplier Effect of Religious Activities on Local Economic Empowerment: Perspectives from Maqashid Syariah and Marketing Mix - Retno Dewi Zulaikah; Cepy Nurmalia Wahyuningtias, Lukita Permanasari, Surya Jawara (YUME : Journal of Management, 2025)
This study aims to identify the forms of economic activities generated by Majelis Sabilu Taubah that impact the improvement of the local economy, to analyze the factors influencing the effectiveness of the multiplier effect from Majelis Sabilu Taubah’s activities in enhancing the local economy, and to examine the challenges and opportunities in optimizing the multiplier effect of these economic activities for sustainable community empowerment from the perspective of maqashid sharia. The approach used in this study is qualitative with a descriptive research method.Data collection was carried out through observation, interviews, and documentation. Observation involved directly monitoring the improvement of community welfare around the Sabilu Taubah Majelis Ta’lim due to the routine religious gatherings led by Gus Iqdam in Karanggayam Village, Srengat District, Blitar Regency. Interviews were conducted with informants related to the existence of Gus Iqdam’s routine religious gatherings at Majelis Sabilu Taubah. Relevant documents regarding the activities of these gatherings were also collected.The results show that Majelis Sabilu Taubah’s activities have created a significant economic impact for the community of Karanggayam Village. Attendance of up to 20,000 people during major events stimulates the growth of culinary businesses, parking services, and lodging, with economic turnover per routine gathering ranging from IDR 12.5 million to IDR 27.4 million. The multiplier effect occurs through direct impacts on vendors, indirect impacts on suppliers, and long-term effects such as changes in livelihoods and the strengthening of social capital through 250 regular volunteers. Challenges include the dominance of local elites, limited capacity of MSMEs, and the community’s dependence on routine religious activities. Meanwhile, opportunities arise from strong social capital, digitalization, and alignment with maqashid sharia principles (hifz al-din, hifz al-mal, hifz al-nafs). Economic activities naturally implement the marketing mix (4P), with relevant products, fair prices, strategic locations, and promotion based on the jamaah network, thereby strengthening the multiplier effect in an ethical and sustainable manner. Keywords: Majelis Sabilu Taubah, Marketing Mix, Multiplier Effect, Community Empowerment, Maqashid Syariah.